2022
DOI: 10.3390/nu14040880
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association of Serum Folate Level with Metabolic Syndrome and Its Components in Korean Premenopausal Women: Findings of the 2016–2018 Korean National Health Nutrition Examination Survey

Abstract: Research on the association of serum folate levels with metabolic syndrome (MetS) in premenopausal women is lacking. This study was aimed to investigate this association in 1730 premenopausal women using the 2016 to 2018 Korean National Health and Nutrition Examination Survey data. Participants’ mean age and BMI were 35.9 years and 22.7 kg/m2, respectively. Participants were divided into three groups according to serum folate tertiles. Odds ratios (OR) and 95% confidence intervals (CIs) for abdominal obesity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Pravenec M et al demonstrated that spontaneously hypertensive rats without folic acid intake exhibited a variety of pathological features of MetS, including hepatic ectopic fat accumulation, glucose tolerance, elevated systolic blood pressure, and significant oxidative stress (36). A study by Koo et al based on the nutritional health survey data from 1,730 pre-menopausal women in Korea found that serum folate levels were significantly associated with MetS prevalence, abdominal obesity, triglyceride levels, and low high-density lipoprotein (37). Another cross-sectional study showed similar results in a group of older adults at higher cardiometabolic risk, with higher folic acid intake associated with lower MetS scores and other metabolic risk factors (38).…”
Section: Vitamin B9 and Metsmentioning
confidence: 99%
“…Pravenec M et al demonstrated that spontaneously hypertensive rats without folic acid intake exhibited a variety of pathological features of MetS, including hepatic ectopic fat accumulation, glucose tolerance, elevated systolic blood pressure, and significant oxidative stress (36). A study by Koo et al based on the nutritional health survey data from 1,730 pre-menopausal women in Korea found that serum folate levels were significantly associated with MetS prevalence, abdominal obesity, triglyceride levels, and low high-density lipoprotein (37). Another cross-sectional study showed similar results in a group of older adults at higher cardiometabolic risk, with higher folic acid intake associated with lower MetS scores and other metabolic risk factors (38).…”
Section: Vitamin B9 and Metsmentioning
confidence: 99%
“…Clinical observational data indicate an association of low concentrations of folic acid with adiposity, body mass index (BMI) and insulin resistance in overweight and obesity (5). Epidemiologi-cal studies have shown that a low dietary folate intake or its low serum levels are highly prevalent in either populations or in obese individuals and are thus linked to an increase in BMI and abdominal fat storage and result in disturbances in glucose and insulin (6)(7)(8). Although it is currently not clear whether folic acid deficiency is a cause or a consequence of obesity, folate supplementation may have a considerable positive impact on obesity and metabolic syndrome (9) by inhibiting inflammation and oxidative stress induced by a high-fat diet (10,11), reducing homocysteine levels and insulin resistance, and altering epigenetic modifications of genes associated with fat and energy metabolism (12,13).…”
mentioning
confidence: 99%